The sea : exploring life on an ocean planet - Plisson, Philip (H.N. Abrams, 2003)
Text and photographs of storms, ports, pollution, diving, rescues, surfing, lighthouses, tides, and many kinds of boats, plants, and animals reveal the world's oceans and the people who live on or near them.